An immunogenic cell death-related classification predicts prognosis and response to immunotherapy in kidney renal clear cell carcinoma - Wang, Licheng; Zhu, Yaru; Ren, Zhen; Sun, Wenhuizi; Wang, Zhijing; Zi, Tong; Li, Haopeng; Zhao, Yan; Qin, Xin; Gao, Dacheng; Zhang, Libo; He, Ziyang; et al. (Frontiers in Oncology, 2023)
Immunogenic cell death (ICD) is a form of regulated cell death that activates an adaptive immune response in an immunocompetent host and is particularly sensitive to antigens from tumor cells. Kidney clear cell carcinoma (KIRC) is an immunogenic tumor with extensive tumor heterogeneity. However, no reliable predictive biomarkers have been identified to reflect the immune microenvironment and therapeutic response of KIRC. Therefore, we used the CIBERSORT and ESTIMATE algorithms to define three ICD clusters based on the expression of ICD-related genes in 661 KIRC patients. Subsequently, we identified three different ICD gene clusters based on the overlap of differentially expressed genes (DEGs) within the ICD clusters.In addition, principal component analysis (PCA) was performed to calculate the ICD scores. The results showed that patients with reduced ICD scores had a poorer prognosis and reduced transcript levels of immune checkpoint genes regulated with T cell differentiation. Furthermore, the ICD score was negatively correlated with the tumor mutation burden (TMB) value of KICD. patients with higher ICD scores showed clinical benefits and advantages of immunotherapy, indicating that the ICD score is an accurate and valid predictor to assess the effect of immunotherapy. Overall, our study presents a comprehensive KICD immune-related ICD landscape that can provide guidance for current immunotherapy and predict patient prognosis to help physicians make judgments about the patient's disease and treatment modalities, and can guide current research on immunotherapy strategies for KICD.